The epidemiology of injuries to the nervous system resulting from sport and recreation - Toth, C. (Physical Medicine & Rehabilitation Clinics of North America, 2009)
Sports and recreational activities are associated with a variety of injuries. Although many of these injuries are musculoskeletal in nature, both the peripheral nervous system and the central nervous system are at risk for injury as well. This article examines the incidence of nervous system injuries in particular sports. The association between particular forms of injuries and the sports in which they are likely to be incurred are also investigated. Further assessment of preventative measures is provided when possible.